2015
DOI: 10.1117/12.2079107
|View full text |Cite
|
Sign up to set email alerts
|

In vitroandin vivoantitumor efficacy of berberine-nanostructured lipid carriers against H22 tumor

Abstract: Hepatocarcinoma, a malignant cancer, threaten human life badly. It is a current issue to seek the effective natural remedy from plant to treat cancer due to the resistance of the advanced hepatocarcinoma to chemotherapy. Berberine (Ber), an isoquinoline derivative alkaloid, has a wide range of pharmacological properties and is considered to have anti-hepatocarcinoma effects. However its low oral bioavailability restricts its wide application. In this report, Ber loaded nanostructured lipid carriers (Ber-NLC) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In this investigation, we first studied the effect of Ber-SLN on H22 tumor to assess if SLN could enhance Ber anti-cancer effects. The present study showed that Ber reduced tumor weight in H22 tumor-bearing mice, which were consistent with other studies [25] . The therapeutic effects of Ber-SLN were obviously improved when prepared with SLN.…”
Section: Conclusion and Discussionsupporting
confidence: 94%
“…In this investigation, we first studied the effect of Ber-SLN on H22 tumor to assess if SLN could enhance Ber anti-cancer effects. The present study showed that Ber reduced tumor weight in H22 tumor-bearing mice, which were consistent with other studies [25] . The therapeutic effects of Ber-SLN were obviously improved when prepared with SLN.…”
Section: Conclusion and Discussionsupporting
confidence: 94%
“…In this respect, Meng et al designed BBR-loaded NLCs and found that BBR-NLC efficiently reduced the development of HepG2, Huh7, and EC9706 malignant cells of humans in vitro and also demonstrated that the potential of NLCs to improve the effectiveness of BBR was likely mainly due to increased bioavailability and blood levels [155]. Wang et al prepared BBR-loaded NLCs and observed that BBR-NLCs considerably reduced H22 cell proliferation in vitro and showed significant anticancer action in in vivo models with respect to bulk BBR solution [156].…”
Section: Nanostructured Lipid Carriersmentioning
confidence: 99%
“…In addition, varieties of nanoparticle carriers have been discovered and used to enhance solubility and Berberine’s bioavailability. For example, nanostructured lipid carriers (NLCs) [ 137 , 138 ], micelles [ 139 ], and other lipid-based nanoparticles were shown to enhance oral bioavailability, solubility, and therapeutic outcome via Berberine’s encapsulation. Similarly, dendrimers [ 140 ], nanogels [ 141 ], chitosan [ 142 ], and all other polymeric-based nanoparticle carriers were also shown to improve Berberine’s pharmacokinetics.…”
Section: Limitations and Future Perspectivementioning
confidence: 99%